Hydroxyapatite/NiFe2O4 superparamagnetic composite: Facile synthesis and adsorption of rare elements. (March 2019) - Attia, Mohamed A.; Moussa, Saber I.; Sheha, Reda R.; Someda, Hanan H.; Saad, Ebtsam A.
Abstract: A magnetic hydroxyapatite composite (CaHAP/NF) derived from calcium hydroxyapatite [Ca10 (PO4 )6 (OH)2 ] and nickel ferrite [NiFe2 O4 ] was successfully synthesized by a coprecipitation method. The synthesized composite was characterized using Fourier transform infrared spectroscopy (FT–IR), X-Ray diffractometer (XRD), thermogravimetric differential thermal analysis (TG-DTA), scanning electron microscopy (SEM) and vibrating sample magnetometer (VSM). Results clarify that the composite is a crystalline in nature, thermally stable up to 800 °C and possesses a high porous structure. The synthesized CaHAP/NF composite is a superparamagnetic material easily separated from aqueous solutions and would dissociate to some extent in strongly acidic conditions. The synthesized material was successfully applied as a solid phase for separation of Eu(III) and Tb(III) ions from aqueous solutions. The effect of various parameters (e.g. solution pH, equilibrium time and ionic strength) on sorption process was studied in static conditions. The synthesized sorbent could be considered as an efficient candidate for separation and recovery of Eu(III) and Tb(III). The sorption process was very fast initially, reached equilibrium within 6 h of contact and independent of ionic strength. The maximum sorption capacity values were 137.35 and 130.43 mg g –1 for Eu(III) and Tb(III), respectively. Desorption of Eu(III) and Tb(III) from loaded sample was studied using various eluents and maximum recovery was obtained using FeCl3 and EDTA solutions. More importantly, both FeCl3 and EDTA were individually applied as eluents in chromatographic separation of Eu(III) and Tb(III) in CaHAP/NF packed column and the best separation results were obtained by EDTA. Highlights: A superparamagnetic hydroxyapatite composite (CaHAP/NF) was successfully synthesized. The composite is a crystalline in nature, possesses a high porous structure and chemically stable at pH > 3.5. 152+154 Eu and 160 Tb radionuclides were effectively removed using the synthesized magnetic composite. REEs were sufficiently recovered using FeCl3 and EDTA as eluents. The chromatographic separation of Eu(III) from Tb(III) was significantly attained using EDTA.